1993
DOI: 10.1105/tpc.5.5.523
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Signal Is Transduced via Protein Phosphorylation Events in Plants.

Abstract: A plethora of abiotic and biotic environmental stresses exert their influence on plants via the gaseous hormone ethylene. In addition, aspects of plant development and climacteric fruit ripening are regulated by ethylene. Sensitivity to ethylene is presumably mediated by a specific ethylene receptor whose activation signal is then transduced via an unknown cascade pathway. We have used the plant pathogenesis response, exemplified by the induction of pathogenesis-related (PR) genes, as a paradigm to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(94 citation statements)
references
References 31 publications
8
86
0
Order By: Relevance
“…In aerated roots, ethylene increased L p within 15 min (Fig. 2), similar to the phosphorylation effect observed in tobacco leaves (Raz and Fluhr, 1993). The ethyleneinduced increase in L p of aspen was significantly reversed by the application of STS, which strongly and noncompetitively binds ethylene (Beyer, 1976).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In aerated roots, ethylene increased L p within 15 min (Fig. 2), similar to the phosphorylation effect observed in tobacco leaves (Raz and Fluhr, 1993). The ethyleneinduced increase in L p of aspen was significantly reversed by the application of STS, which strongly and noncompetitively binds ethylene (Beyer, 1976).…”
Section: Discussionsupporting
confidence: 69%
“…There is, however, evidence that ethylene induces a rapid and transient protein phosphorylation in tobacco leaves, and a protein kinase inhibitor, H-7,1-(5-isoquinolinylsulfonyl)-2-methylpiperazine, blocked ethylene-induced pathogenesis-related protein accumulation (Raz and Fluhr, 1993). A rapid change in the pattern of protein phosphorylation was also induced by ethylene in pea epicotyls (Berry et al, 1996) and H-7-sensitive protein kinase(s) was found to be involved in ethylene-induced protein phosphorylation in pea seedlings (Kwak and Lee, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ethyphon-, ACC-and ethylene-induced TTS mRNA-shortening in unpollinated styles (Figures 8, 9), and the inhibition of pollination-induced TTS mRNA-shortening by the ethylene action-blocker STS (Figure 6b and c) indicate that ACC and ethylene are intimately involved in this response. The induction of TTS mRNA-shortening in unpollinated styles by the phosphatase inhibitor okadaic acid (Figure 8) is also consistent with this response being an ethylene-related phenomenon, since protein phosphorylation has been shown to be involved in the transduction of at least a few other ethyleneinduced responses (Raz and Fluhr, 1993).…”
Section: The Role Of Ethylene and Acc In Polfination-induced Transmitsupporting
confidence: 74%